Molecular characterisation of ToLCNDV isolates causing yellow mosaic disease in gourds of Karnataka - Bhavana, S; Patil, S; Naik , R G; Manjunatha, H (Plant Science Today, 2026)
Yellow mosaic disease (YMD) is a major constraint in cucurbit production in India. The present study was undertaken to detect and characterise begomoviruses associated with YMD in ridge gourd (Luffa acutangula (L.) Roxb.), bitter gourd (Momordica charantia L.), ivy gourd (Coccinia grandis (L.) Voigt) and bottle gourd (Lagenaria siceraria (Molina) Standl.) from Chikmagalur, Davanagere and Shivamogga districts of Karnataka in the year 2021. Polymerase chain reaction (PCR) amplification using degenerate primers DengA/DengB and PAL1v/PAR1c confirmed the presence of begomovirus, amplifying expected fragments of 560 bp and 1.2–1.3 kb, respectively. Sequencing and BLASTn analysis confirm the presence of Tomato leaf curl New Delhi virus (ToLCNDV). Phylogenetic analysis showed clustering of isolates based on host and region. The ridge gourd (MZ664277), bitter gourd (MZ664278) and ivy gourd (MZ664279) isolates grouped closely, while the bottle gourd (MZ664281) formed a distinct cluster. Identity analyses confirmed 96–100 % sequence similarity with known ToLCNDV strains. The study establishes ToLCNDV as the predominant etiological agent of YMD in these cucurbits in Karnataka.